بعض الخواص النوويه لنظائر الجرمانيوم 68,70,72Ge ذات التناظر الديناميكي U(5)باستخدام نموذج IBM-1 - عبد الوهاب, علي (University of Thi-Qar Journal of Science, 2008)
Interacting boson model (IBM-1) was used in the present work to study some of nuclear structures for selected Germanium isotopes(A=68,70,72) which have vibrational motion of the U(5) dynamical symmetry. These isotopes have been classified to be dynamical symmetry by comparing the experimental energy levels which taken from the references with the ideal chart for the three dynamical symmetry U(5) , O(6) , SU(3) , and energy ratios E(41+)/E(21+) , E(61+)/E(21+) , E(8 with the ideal values. Therefore are calculated the energy levels and gamma transitions for these isotopes depending on the total number of boson (N). reduced transition probabilities and their matrix element T(E2) were calculated, these results help to calculate electric quadruple moment (Q ). The results compared with the available experimental data were they show good agreement.